2011
DOI: 10.1093/jac/dkr444
|View full text |Cite
|
Sign up to set email alerts
|

Clofazimine: current status and future prospects

Abstract: Clofazimine, a lipophilic riminophenazine antibiotic, possesses both antimycobacterial and anti-inflammatory activities. However, its efficacy has been demonstrated only in the treatment of leprosy, not in human tuberculosis, despite the fact that this agent is impressively active in vitro against multidrug-resistant strains of Mycobacterium tuberculosis. Recent insights into novel targets and mechanisms of antimicrobial and anti-inflammatory activity coupled with the acquisition of innovative drug delivery te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
293
0
10

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(307 citation statements)
references
References 71 publications
4
293
0
10
Order By: Relevance
“…phage dependent, active xenobiotic sequestration response associated with the intracellular accumulation of clofazimine, the upregulation of IL-1RA (34,35,52) could explain the potent antiinflammatory effects of clofazimine reported in clinical studies (3,4). IL-1RA inhibits the binding of soluble IL-1␣ and IL-1␤ to the proinflammatory interleukin-1 (IL-1) receptor (34,35,52), leading to a pronounced, systemic anti-inflammatory activity.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…phage dependent, active xenobiotic sequestration response associated with the intracellular accumulation of clofazimine, the upregulation of IL-1RA (34,35,52) could explain the potent antiinflammatory effects of clofazimine reported in clinical studies (3,4). IL-1RA inhibits the binding of soluble IL-1␣ and IL-1␤ to the proinflammatory interleukin-1 (IL-1) receptor (34,35,52), leading to a pronounced, systemic anti-inflammatory activity.…”
Section: Figmentioning
confidence: 99%
“…lofazimine is an orally bioavailable, poorly soluble, highly lipophilic (logP Ͼ 7) antibiotic drug with a very long pharmacokinetic half-life (1)(2)(3)(4)(5)(6). It was first marketed in 1969 as "Lamprene," and in 1983 it was recommended by the World Health Organization as one of the components of multidrug therapy against leprosy (7).…”
mentioning
confidence: 99%
“…We also concluded that an electron-withdrawing group at the para-position of the phenyl ring at the N-5 position was beneficial to antituberculosis activity [9]. Previously, O'Sullivan and coworkers found that compounds bearing a 3,4-dichlorophenyl or 3,4,5-trichlorophenyl group at the N-5 position and a tetramethylpiperidyl group at the C-3 position, such as compound B4100 (Figure 1), possessed improved antituberculosis activity as compared to CFZ [10,11]. These work prompted us to further investigate the effect of the halogen atoms on the phenyl ring at the N-5 position for antituberculosis activity based on our 2-methoxypyridylamino-substituted riminophenazine system.…”
Section: Introductionmentioning
confidence: 98%
“…The antimycobacterial riminophenazine agent clofazimine is categorised by the World Health Organization (WHO) as a last-resort option (group 5 drug) in the treatment of multidrug-resistant TB (MDR-TB), largely because of its poor pharmacokinetic properties [12,13]. However, this antibiotic possesses several properties that may enable it to target both biofilm-forming as well as biofilminsulated organisms, including those that are MDR [12][13][14].…”
mentioning
confidence: 99%
“…However, this antibiotic possesses several properties that may enable it to target both biofilm-forming as well as biofilminsulated organisms, including those that are MDR [12][13][14]. Foremost amongst these are its lipophilicity and low-level resistance profile, as well as recently described inhibitory activity against mycobacterial persisters [15][16][17][18].…”
mentioning
confidence: 99%